KONSEP MASHLAHAH PERSPEKTIF MUHAMMAD SA’ÎD RAMADHÂN AL-BÛTHÎ - Maimun Nawawi (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2010)
Mashlahah is often made identically with benefit. It hasplaced in one of fields in Islamic law study, especially inushûl al-fiqh. It has a role in determining a debatable lawconclusion. It is also as essence of maqâshid al-syarî’ah thatis needed in every law consideration. The problem ishow to determine a law illah that has mashlahah, and whohas a role in determining and assessing mashlahah, onlyGod (syari’) or mukallafkah, if mukallaf has a right, how farit has its power to determine a mashlahah in certain lawcontext. This writing will give its description.